2016
DOI: 10.1080/13854046.2016.1172667
|View full text |Cite
|
Sign up to set email alerts
|

Ecological validity of executive function tests in moderate traumatic brain injury in Ghana

Abstract: This study has shown that although EF test scores, specifically the Stroop Test, TMT and EF composite scores, can be used to predict real-world behavior after moderate TBI in Ghana, such predictions are likely to be limited. The general implication for cross-cultural neuropsychology is that the (limited) ecological validity of EF tests may not necessarily be affected by whether the tests were administered in settings where they have not been standardized. This argument is, however, tenable granted that the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…But there is a dissenting view in the ndings of this study 61 . Socio-Cultural patterns might contribute to the noted discrepancy in endorsing self-reported cognitive di culties 62 . While recall bias might be a factor, in Oman and some other cultures from the East, what is known as introspective is generally not patterned in society 63 .…”
Section: Discussionmentioning
confidence: 99%
“…But there is a dissenting view in the ndings of this study 61 . Socio-Cultural patterns might contribute to the noted discrepancy in endorsing self-reported cognitive di culties 62 . While recall bias might be a factor, in Oman and some other cultures from the East, what is known as introspective is generally not patterned in society 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the ecological validity has been studied by correlating scores on self-reported scales with traditional parameters of laboratory tasks such as mean reaction time, reaction time variability, and/or a number of errors (Chaytor and Schmitter-Edgecombe 2003; Lamberts et al 2010). So far, the literature shows weak or no relation between daily life and laboratory measures of executive functions (Adjorlolo 2016), questioning the ecological validity of laboratory tests. In line with the literature, the present study addressed a rarely used laboratory measure in ecological validity studies, namely PES as a measure of task-related error monitoring, and PES showed only a weak association with planning, but not with other measures of executive functioning and real world behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For detailed methodological descriptions, see Adjorlolo (2016). Briefly, a total of 50 (male = 35, female = 15) TBI patients was recruited from the outpatient clinics at Korle-Bu Teaching Hospital (KBTH; n = 30) and 37 Military Hospital ( n = 20) in Accra, the capital of Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…The data reported here were collected as part of a project investigating the ecological validity of EF tests in Ghana (see Adjorlolo, 2016). The data collection process complied with the guidelines and regulations of the University of Ghana Medical School Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation